2022
DOI: 10.1590/1806-9282.20210874
|View full text |Cite
|
Sign up to set email alerts
|

Oral dydrogesterone in frozen-thawed embryo transfer cycles

Abstract: OBJECTIVE:The aim of this study was to compare the use of micronized vaginal progesterone and oral dydrogesterone in the endometrial preparation for frozen-thawed embryo transfer. METHODS:This was a randomized, controlled, open, two-armed clinical trial, with women undergoing frozen-thawed embryo transfer along with hormone replacement therapy for endometrial preparation, between September 2019 and February 2021. A total of 73 patients were randomly selected and orally administered 40 mg/day dydrogesterone (dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, a 2022 study showed that the use of micronized vaginal progesterone 800 mg/day and oral dydrogesterone 40 mg/day for endometrial preparation in FET cycles had similar reproductive outcomes ( P =0.196) [ 73 ]. In 2021, 2 trials on programmed FET cycles provided a similar conclusion regarding the progesterone level on the day of embryo transfer [ 54 , 55 ].…”
Section: Progesterone and Luteal-phase Support In Programmed Cycles O...mentioning
confidence: 99%
“…However, a 2022 study showed that the use of micronized vaginal progesterone 800 mg/day and oral dydrogesterone 40 mg/day for endometrial preparation in FET cycles had similar reproductive outcomes ( P =0.196) [ 73 ]. In 2021, 2 trials on programmed FET cycles provided a similar conclusion regarding the progesterone level on the day of embryo transfer [ 54 , 55 ].…”
Section: Progesterone and Luteal-phase Support In Programmed Cycles O...mentioning
confidence: 99%